Investigation on cyclic degradation of thermophysical properties of paraffin wax as a phase change material and their impact on heat storage performance - Anusuiah, Vasu (2021)
Thermo-physical property study of the Phase Change Material (PCM) is necessary to build an efficient latent heat thermal energy storage system (LHTESS). The stability of thermophysical property due to repeated thermal cycling is an essential factor that has to be studied to find a promising latent heat storage material with a long-duration lifetime. Void formation during the solidification process in thermal cycling is an unwanted property in the PCM. This study concentrates on the void formation due to repeated thermal cycling and its impact on thermo-physical property degradation of paraffin wax. Paraffin wax with the melting temperature in the range of 58oC to 62oC is selected as PCM. Whereas Al2O3 and CuO nanoparticles of 20-40 nm size are selected as nanoparticle additive for this study. The nano-PCM composite and hybrid nano-PCM composite samples are prepared by mixing 5 wt% of Al2O3, 5 wt% of CuO and 2.5 wt% Al2O3+2.5 wt% CuO nanoparticles with paraffin wax by bottom heating and natural cooling at ambient temperature. Samples are made to undergo 1, 50, 100, 150, and 200 thermal cycles. Morphology of the samples is studied using a Scanning Electron Microscope (SEM). The thermal properties are analysed by Differential Scanning Calorimeter (DSC). Thermal Gravimetric Analyser (TGA) is used to analyse the thermal stability and reliability. Thermal conductivity is measured using KD2 Pro thermal properties analyser. Viscosity and density is also measured using Rheometer Kinexus Lab+ and Archimedes principle to observe the impact of void formation during solidification shrinkage. Void formation in samples is quantified with help of ImageJ software. Results have revealed that nanoparticles addition has reduced the void variation by 16.8% in the hybrid-PCM composite (2.5 wt% Al2O3+2.5 wt% Cuo-PCM) after 200 thermal cycles. The void ratio is fluctuated with the thermal cycle in all the samples and has an inverse relation with all the thermophysical properties measured. The percentage of void ratio variation after C200 compared to C1 in hybrid-PCM is -16.7%,which is the least value calculated among all the samples. CuO nanoparticle addition has shown 23.3%, 23.2% and 22.25% increment in latent heat of melting, solidification and peak degradation temperature, respectively. Hybrid–PCM has shown an improvement in thermal conductivity, viscosity and density by 5.43%, 9.58% and 4.07%, respectively. Peak degradation temperature value has increased by 13.4%, 22.25% and 6.43% compared to PCM by addition of Al2O3, CuO and hybrid nanoparticles, respectively. Compared to other samples, hybrid-PCM is more stable and has shown consistency in all the thermophysical properties throughout all the thermal cycles. Paraffin wax with 2.5 wt% Al2O3+2.5 wt% CuO nanoparticles is found to be a better energy storage material in LHTESS. An addition of surfactant is recommended to improve the stability of nanoparticle distribution in nanoparticle-PCM composites. Thermophysical property improvement and stability achievement in paraffin wax by the incorporation of 2.5 wt% Al2O3+2.5 wt% CuO nanoparticles have contributed to eliminating the limitations in the life span of paraffin wax usage in thermal energy storage applications.